The Emperor has no clothes: A critique of Safety-II. (August 2022) - Cooper, M.D.
Highlights: Resilience is an epiphenomenon not a system property, therefore Safety-II cannot exist as a concept. All New-View methodologies and practices are Safety-1; there is nothing new. New-View is unsupported: There is no peer-reviewed evidence to show any impact on OSH. New-view philosophies are diametrically opposed to Safety-1, making reconciliation difficult. The OSH profession and safety science is suffering from a crisis of ethics. Abstract: Relatively new to safety, Resilience Engineering (RE) is known by various pseudonyms: Safety-II, Human & Organizational Performance (HOP) and Safety Differently. Collectively termed New-View, they have created a stir amongst OSH practitioners by challenging them to view key areas of occupational safety in a different way: [1] how safety is defined; [2] the role of people in safety; and [3] how businesses focus on safety. When subject to critical scrutiny, New-View's major tenets are shown to be a collection of untested propositions (ideas, rules, and principles). New-view's underlying RE philosophy is predicated on repeatedly testing the boundary limitations of systems until a failure occurs, which paradoxically requires more risk controls that create the very problems New-View criticizes and attempts to address – constraints, complexity, rigidity, and bureaucracy. This continuous threat-rigidity cycle indicates New-View's raison d'etre is somewhat circular. New-View entirely lacks any new associated practical methodologies for improving safety performance: it uses traditional Safety-1 methodologies to tackle actual safety problems. Moreover, no published, peer-reviewed empirical evidence demonstrates whether or not any aspect of New-View's propositions are valid. Currently we don't know how, or if, New-View improves safety performance per se, or if it reduces or eliminates incidents/injuries. The extant Safety-1 literature suggests that New-View's propositions lack substance. The inescapable conclusion, therefore, is 'the emperor has no clothes' and that ideology and emotion has triumphed over science and practice. It is also clear that the OSH profession has an immense crisis of ethics across its entire landscape.